Perbaikan kualitas produk genteng di UMKM SOKKA STR dengan Metode Seven Steps - Chalista, Lidwina Alma; Hadisantono; Anggoro, Paulus Wisnu (Jurnal Teknik Industri dan Manajemen Rekayasa, 2025)
[Improving Clay Roof Tile Product Quality at SOKKA STR MSME Using the Seven Steps Method] SOKKA STR is a clay roof tile manufacturer located in Godean, Sleman, Yogyakarta, which still uses traditional production methods. This has led to a high defect rate, especially during periods of increased demand. This study aims to identify the causes of defects and propose solutions to reduce the defect rate to below 1%. The method used is the seven steps approach supported by the seven tools due to its simplicity, structured process, and low investment requirement. An analysis of production data from 2022–2024 shows a defect rate of 3%–5%, including cracks, breaks, chips, and burnt coloration. The main causes are human factors, methods, materials, and environmental conditions. Proposed solutions include setting production targets, routine supervision, technical training, inspection of the firing process, use of clay filtering tools, proper selection and drying of firewood, standardization of procedures, provision of temperature measuring devices, and organized firewood arrangement. These measures are expected to sustainably improve the quality of tile production.